Statistical optimization of bioethanol production from empty fruit bunches by a mixed culture of yeast and fungus - Alam, Md. Zahangir; Zainal, Nur Hidayah; Al-Khatib, Ma'an Fahmi Rashid (2014)
Production of bioethanol from oil palm empty fruit bunches (EFB) by Saccharomyces cerevisae and Aspergillus niger is among the ways of reducing environmental pollution and consumption of crude oil. This study used sequential optimization approach based on statistical experimental design including Plackett-Burman (PB) design, one-factor-at-a-time (OFAT) and face-centered central composite design (FCCCD). Plackett-Burman design was used to screen the important medium components and process conditions that influence the bioethanol production. The three parameters chosen based on the PB analysis for determination of optimum values by response surface methodology (RSM) were pH, KH2PO4 and agitation. The validity of the model was verified and the optimum value of pH 5.5, agitation of 150rpm and 0.3% of KH2PO4 led to a maximum bioethanol production of 7.4 g/l.